PENERAPAN MEDIA VIDEO ANIMASI SEBAGAI SARANA PEMBELAJARAN PEMAHAMAN BERCERITA SISWA KELAS 5 DI SDN 32 RANTAU BAYUR - Dini Firliana; Bambang Hermansah; Ferri Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem in this study is How is the Application of Animated Audio Visual Media to the Comprehension of Storytelling of Grade 5 Students?. This study aims to determine the application of animated audio visual media as an aid to the comprehension of storytelling of grade 5 students. This study uses a qualitative method. This study uses data collection techniques in the form of observation, interviews, and documentation. Based on research on the application of animated audio visual media as an aid to the comprehension of storytelling of grade 5 students of SDN 32 Rantau Bayur, it can be concluded that the use of animated audio visual media in storytelling learning is effective in helping to improve students' understanding of the content of the story. This media presents material in an interesting, interactive, and easy-to-digest manner by students. Students' responses to animated media are also very positive, they show enthusiasm, activeness, and concentration during the learning process. This proves that animated media is able to create learning that is not boring. The evaluation results show an increase in student understanding, which can be seen from their ability to describe the contents of the story, understand moral messages, and answer questions. In addition, this media also shapes students' character through moral values in the story that can be applied in everyday life.